AKTUALISASI DAKWAH ISLAM (Kajian Analisis Formulasi Dakwah Rasulullah) - Muhammad Barmawi (Religia, 2016)
Rasulullah SAW. is a success in conveying Islam to all people. Thus it shows about good methods of propaganda that has delivered the Prophet. Therefore, modeled on the Prophet preaching methods is critical to the continued sustainability of the Islamic religion. However, the method should be updated in accordance with current conditions, so that the propagation of Islam received perfectly. This paper aims to reveal the character of propaganda is effective, namely by looking at the formulation of Islamic propaganda ever Prophet. in the midst of a multidimensional society. with reference to the arguments syar'i particular hadith of the Prophet, then actualize with today's modern era. To uncover these data, the authors use the method of content analysis, with history’s approach. Based on the data obtained by the author, the conclusion can be classified into several sections: First, the terminology defendant aimed convey religious messages to improve the lifestyle of each individual or group. Second, the mechanism of propaganda that must be done is to; a). Moral good, b). Oral, c). Qital. Third, In actualize propaganda, is required to see the condition and situation of the object of propaganda, both in the context of micro and macro